LITERATURE REVIEW : HUBUNGAN PANDEMI COVID-19 TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL - Hasna Tri Rachmatika; Libna Aththohiroh; Radi Radi; Dwi Sarwani Sri Rejeki (Dian Nuswantoro Semarang, 2021)
The Covid-19 pandemic has occurred since December 2019 which disrupted various human activities. The high rate of transmission of this virus has resulted in anxiety in the wider community about being exposed to Covid-19, including pregnant women. Based on these conditions, a study was conducted which aims to determine the relationship between the Covid-19 pandemic and the anxiety level of pregnant women. The research was conducted using the literature review method from journals published between 2016—2021, both nationally and internationally. Data obtained from databases include ScienceDirect, PubMED, and Google scholar with the keywords pandemic, Covid-19, pregnant women, anxiety, mental health, prenatal, pregnant women, anxiety levels. The results of the literature study obtained nine articles that match the inclusion and exclusion criteria. From the review of the article, it is known that the Covid-19 pandemic has increased anxiety for pregnant women that related to restrictions on outside activity, economic decline, and the possibility be exposed to the Covid-19. This research is expected to be useful in determining the level of anxiety of pregnant women during a pandemic during childbirth, thus it can be used as evaluation material fo related parties to determine the best solution in overcoming this anxiety.